Synthesis of Ag-Pt alloy nanoparticles in aqueous bovine serum albumin foam and their cytocompatibility against human gingival fibroblasts - Singh, A. V.; Patil, R.; Kasture, M. B.; Gade, Wasudeo N.; Bhagavatula L. V. Prasad (Colloids and Surfaces B-Biointerfaces, 2009)
Foams of bovine serum albumin (BSA) have been utilized for synthesizing in situ protein capped Ag-Pt alloy nanoparticles. The in vitro cytotoxicity and the rate of proliferation of human gingival fibroblasts (HGFs) in presence of the above synthesized alloy nanoparticles is investigated. Expression profile of protein involved in detoxification, i.e. metallotheonein (MT) were assayed by ELISA and expression of mRNA transcripts by reverse transcription polymerase chain reaction (RT-PCR). Cytotoxicity results suggested that protein capped nano-alloys might be promising candidates for implants and prosthetic material. RT-PCR and ELISA confirmed the expression of MT. in cells treated with the alloy nanoparticles. Morphology variation studied by SEM also confirms that cells treated with alloy nanoparticles present an intact morphology. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Alloy nanoparticles; Biocompatibility; ELISA; Human gingival fibroblasts; mRNA; Protein foams

Development of non-woven nanofibers of egg albumen-poly (vinyl alcohol) blends: influence of solution properties on morphology of nanofibers - Rathna, Gundloori Venkata Naga; Jog, Jyoti Prakash; Gaikwad, A. B. (Polymer Journal, 2011)
Egg albumen (EA), a highly functional globular protein with desirable properties, is the least-explored material for biomaterial applications, although it is available in abundance. In our studies, we explored the viability of EA and various blends with biocompatible and non-toxic poly (vinyl alcohol) (PVA) to produce nanofibers for biomedical applications. EA and PVA blends were prepared in various compositions. Electrospinning was used to fabricate non-woven nanofibers. Solution properties, such as viscosity and electrical conductivity, were evaluated for various prepared solutions. Solution viscosity increased with increasing polymer concentration. Solutions with higher contents of EA recorded increased conductivity, which decreased with increasing PVA content. The influence of solution properties on the morphological appearance of as-spun products was studied using scanning electron microscopy. Instead of nanofibers, nanoparticles and microparticles of EA were produced at even higher contents. In contrast, a gradual increase in the addition of PVA content to 8% EA solution resulted in the transformation of particles from large agglomerates to very fine fibers (approximate to 100nm in diameter) because of the influence of polymer content, viscosity and conductivity. The polymer-polymer interactions in the prepared materials have been validated by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction and gel electrophoresis. Polymer Journal (2011) 43, 654-661; doi:10.1038/pj.2011.34; published online 18 May 2011
Keywords: Biocompatibility; biodegradable; blends; nanotechnology; Proteins

Synthesis and drug-delivery behavior of chitosan-functionalized graphene oxide hybrid nanosheets - Rana, Vijay Kumar; Choi, Myeon-Cheon; Kong, Jin-Yeon; Kim, Gwang Yeon; Kim, Mi Ju; Kim, Sun-Hee; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Macromolecular Materials and Engineering, 2011)
Chitosan-functionalized graphene oxides (FGOCs) were successfully synthesized. FGOCs were found to significantly improve the solubility of the GO in aqueous acidic media. The presence of organic groups was confirmed by means of XPS and TGA. Restoration of the sp(2) carbon network and exfoliation of graphene sheets were confirmed by Raman spectroscopy, UV-visible spectroscopy and WAXD. The SEM and AFM investigations of the resultant FGOCs showed that most of the graphene sheets were individual and few were layered. Controlled release behavior of Ibuprofen and 5-fluorouracil was then investigated. We found that FGOCs are a promising new material for biological and medical applications.
Keywords: Biocompatibility; Chitosan; drug delivery systems; functionalization of polymers; solution properties

Chitosan and chitosan-co-poly(epsilon-caprolactone) grafted multiwalled carbon nanotube transducers for vapor sensing - Rana, Vijay Kumar; Akhtar, Shamim; Chatterjee, Sudipta; Mishra, Satyendra; Singh, Raj Pal; Ha, Chang-Sik (Journal of Nanoscience and Nanotechnology, 2014)
Vapor sensitive transducer films consisting of chitosan grafted (CNT-CS) and chitosan-co-polycaprolactone grafted (CNT-CS-PCL) multiwalled carbon nanotubes were prepared using a spray layer-by-layer technique. The synthesized materials (CNT-CS and CNT-CS-PCL) were characterized by Fourier transform infrared spectroscopy, C-13 CP/MAS solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis. Both CNT-CS and CNT-CS-PCL transducers were analyzed for the response of volatile organic compounds and toluene vapors. The ranking of the relative resistance (A(r)) for both chitosan based transducers were as follows: toluene < chloroform < ethanol < methanol. The CNT transducer (CNT-CS) was correlated selectively with an exponential law to the inverse of Flory-Huggins interaction parameters, chi(12). Dosing the films on the interdigitated electrodes with methanol, ethanol, chloroform and toluene vapors increased the film resistance of CNT-CS but decreased the resistance of CNT-CS-PCL compared to that of the reported transducers.
Keywords: Biocompatibility; Chitosan; MWCNTs; Poly(epsilon-caprolactone); Vapour Sensing

pi-Conjugated chromophore incorporated polystyrene nanobeads as single optical agent for three-channel fluorescent probe in bioimaging application - Makkad, Sarabjot Kaur; Asha, S. K. (ACS Biomaterials Science & Engineering, 2017)
Fluorescent polystyrene (PS) nanobeads in the size range similar to 70-120 nm incorporating perylene bisimide (PBI-PS) and/or oligo(p-phenylenevinylene) (OPV-PS) was developed by miniemulsion polymerization technique. A dye loading content (DLC) of <3% was sufficient to impart high fluorescence emission capability to the PS beads. OPV-PS exhibited emission in the range 400-550 nm with peak emission at 450 nm (lambda(ex) = 350 nm; phi(FL) = 26%); PBI-PS showed emission from 520-650 nm with peak emission at 545 nm (lambda(ex) = 490 nm; phi(FL) = 9.7%) in 1x PBS buffer, whereas OPV(PBI)-PS nanobeads incorporating both the fluorophores exhibited multicolor emission capabilities (lambda(ex) from 350 to 490 nm). The nanoparticles were characterized by field-emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM) and dynamic light scattering (DLS) for size and zeta potential for surface charge. For bioimaging applications, the PS nanoparticles were incubated with HeLa cells. Cell viability analysis involving HeLa cells showed more than 90% cell viability confirming the biocompatibility of the PS The cellular uptake of the nanoparticles was confirmed by flow cytometry analysis and confocal laser scanning microscopy (CLSM) images. The subcellular localization of the nanoparticles in the cytoplasm could be precisely established by their simultaneous multicolor emission. The PS-based single optical agent presented here that can function as three-channel fluorescent probe to meet the requirements for multicolor bioimaging is advantageous.
Keywords: Biocompatibility; bioimaging

Formulation and evaluation of wound healing activity of sophorolipid-sericin gel in wistar rats - More, V. Snehal; Koratkar, Santosh S.; Kadam, Navnath; Agawane, Sachin; Prabhune, Asmita (Pharmacognosy Magazine, 2019)
Sericin is a useful by-product of silk processing and is resistant to oxidation and ultraviolet and can absorb and release moisture easily. Sericin has biological activities such as antibacterial, antioxidant, and tyrosinase inhibition. Sophorolipids are microbial extracellular glycolipids produced by resting cells of Candida bombicola. Sophorolipids show excellent skin compatibility and also have antibacterial property. In this study, we have developed a novel formulation consisting of sericin and sophorolipid with calcium alginate as a binding agent. Since both the ingredients are biocompatible and biodegradable, the formulation was tested for wound healing in Wistar rats. A commercial ointment povidone was used as control. The animal group, treated with sericin and sophorolipid cream, showed fast contraction, rapid closure, and healing when compared with control and commercial ointment. These observations were validated with histopathological studies where more fibroblast proliferation, angiogenesis, and keratinization were observed. This is a green, cost-effective formulation for fast wound healing.
Keywords: Biocompatibility; formulation; sericin; Sophorolipid; wound Healing

Biofilm formation to inhibition: role of zinc oxide-based nanoparticles - Mahamuni-Badiger, Pranjali P.; Patil, Pooja M.; Badiger, Manohar V.; Patel, Pratikshkumar R.; Thorat-Gadgil, Bhagyashi S.; Pandit, Abhay; Bohara, Raghvendra A. (Materials Science & Engineering C-Materials for Biological Applications, 2020)
Zinc oxide nanoparticles have received much attention worldwide as they possess unique properties like varied morphology, large surface area to volume ratio, potent antibacterial activity, and biocompatibility. Biofilm contains homogenous or heterogeneous microorganisms that remain enclosed in a matrix of an extracellular polymeric substance on biotic or abiotic surfaces. Bacterial biofilm formed on medical devices such as central venous catheters, urinary catheters, prosthetic joints, cardiovascular implantable devices, dental implants, contact lenses, intrauterine contraceptive devices and breast implants cause persistent infections. Such biofilm-associated infections in medical implants cause serious problems for public health and affect the function of medical implants. So, there is an urgent need for the use of an antimicrobial agent that will inhibit biofilm, including such antibiotic-resistant bacterial strains as bacteria, to develop multiple drug-resistances resulting in failure of the antibiotic's action. The antimicrobial agent used should be ideal in terms of biocompatibility, antimicrobial activity, stability at different environmental conditions, with less sensitivity to the development of resistance towards micro-organisms, safe for in vivo and in vitro use, and remain non-hazardous to the environment, etc. The first objective of the review discusses the insights into the formation of biofilm on a medical device with the current strategies to inhibit. The second purpose is to review the recent progress in ZnO- based nanostructure including composites for antibacterial and anti-biofilm activities. This will offer a new opportunity for the application of Zinc oxide-based material in the prevention of biofilm on the medical devices.
Keywords: antibacterial activity; Antibiofilm agent; Biocompatibility; Biofilm; Nanocomposites; ZnO nanoparticles

Manipulating hydrophobicity of polyester nanofiber mats with egg albumin to enhance cell interactions - Patel, Pratikshkumar R.; Pandey, Komal; Killi, Naresh; Gundloori, Rathna Venkata Naga (Polymer Engineering and Science, 2021)
A hybrid of poly-l-lactic acid (PLA) and poly-epsilon-caprolactone (PCL) system was designed using hydrophilic generally regarded as safe (GRAS) protein, egg albumin (EA), and fabricated as nanofiber mats (NM) to facilitate improved cell interactions and functionality. Our studies include, preparation and analysis of physicochemical properties of NM. Surface morphology of NM was smooth with the diameter ranging from 250 to 400 nm. The contact angle of NM decreased from 80 to 45 degrees with the increase in EA concentration. The rate and extent of swelling was increased 3-folds with the addition of EA. Release studies of NM showed maximum amount of MTz was released with the increase in MTz concentration (>85%). The MTz interaction with EA and structure stability of EA was confirmed from fluorescence and circular dichroism studies. NM showed increase in inhibition of bacterial growth of Staphylococcus aureus and Escherichia coli with the increase in MTz concentration. Cell viability of the NM was >80% and also, the cell proliferation increased as EA content increased. NM hemolytic activity was less than 5% suggesting compatibility. Hence, results concluded that EA had regulated hydrophobicity, promoted cell interactions, and proliferation and therefore, NM is considered safe for tissue regeneration.
Keywords: Biocompatibility; Biomaterials; drug delivery systems; egg albumin; electrospinning; nanofibers; polyesters

Silk fibroin microparticle scaffold for use in bone void filling: safety and efficacy studies - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (ACS Biomaterials Science & Engineering, 2022)
Silk fibroin (SF) is a natural biocompatible protein polymer extracted from cocoons of silkworm Bombyx mori. SF can be processed into a variety of different forms and shapes that can be used as scaffolds to support bone regeneration. Threedimensional (3D) SF scaffolds have shown promise in bone-void -filling applications. In in vitro studies, it has been demonstrated that a microparticle-based SF (M-RSF) scaffold promotes the differentiation of stem cells into an osteoblastic lineage. The expression of differentiation markers was also significantly higher for M-RSF scaffolds as compared to other SF scaffolds and commercial ceramic scaffolds. In this work, we have evaluated the in vitro and in vivo biocompatibility of M-RSF scaffolds as per the ISO 10993 guidelines in a Good Laboratory Practice (GLP)-certified facility. The cytotoxicity, immunogenicity, genotoxicity, systemic toxicity, and implantation studies confirmed that the M-RSF scaffold is biocompatible. Further, the performance of the MRSF scaffold to support bone formation was evaluated in in vivo bone implantation studies in a rabbit model. Calcium sulfate (CaSO4) scaffolds were chosen as reference material for this study as they are one of the preferred materials for bone-void -filling applications. M-RSF scaffold implantation sites showed a higher number of osteoblast and osteoclast cells as compared to CaSO4 implantation sites indicating active bone remodeling. The number density of osteocytes was double for M-RSF scaffold implantation sites, and these M-RSF scaffold implantation sites were characterized by enhanced collagen deposition, pointing toward a finer quality of the new bone formed. Moreover, the M-RSF scaffold implantation sites had a negligible incidence of secondary fractures as compared to the CaSO4 implantation sites (similar to 50% sites with secondary fracture), implying a reduction in postsurgical complications. Thus, the study demonstrates that the M-RSF scaffold is nontoxic for bone-void -filling applications and facilitates superior healing of fracture defects as compared to commercial calcium-based bone void fillers.
Keywords: Biocompatibility; biological safety; bone void filler; ISO 10993; M-RSF; Serioss; Silk fibroin

Engineered silk matrix as a substitute for acellular dermal matrix in breast reconstruction surgery - Deshpande, Rucha; Shukla, Swati; Kale, Amod; Sayyad, Raeesa; Kewale, Bhawana; Deshmukh, Narendra; Nisal, Anuya; Venugopalan, Premnath (International Journal of Biological Macromolecules, 2025)
Implant-based breast reconstruction is a common standard of care for breast cancer patients following mastectomy. To support implant weight and placement, surgeons utilize autologous tissues, acellular dermal matrices (ADMs), or synthetic meshes. While ADMs provide structural support, they present significant risks, including infection transmission and seroma. Conversely, synthetic meshes exhibit poor cellular adhesion, leading to inadequate tissue integration. To address these challenges, there is a need for a matrix that enhances tissue integration while minimizing infection risks and other complications. Silk fibroin (SF), a natural biopolymer, possesses excellent biocompatibility and mechanical properties. This study introduces a novel engineered silk matrix (ESM) as an advanced solution for soft tissue regeneration, specifically in breast reconstruction surgery. The present study establishes the safety of ESM and evaluates its potential a tissue regeneration matrix through extensive in-vitro and in-vivo analyses. In-vitro assays demonstrated superior cellular adhesion, proliferation of human mammary fibroblast cells (HMFCs), collagen deposition and angiogenesis in ESM compared to collagen matrices and ADMs. Safety assessments, conducted in accordance with ISO 10993 guidelines, confirmed noncytotoxic nature of ESM. Furthermore, subcutaneous implantation revealed no systemic toxicity or adverse tissue reactions. In-vivo studies utilizing a Yorkshire pig model of simulated breast reconstruction surgery, demonstrated superior performance of ESM over collagen matrices in tissue regeneration. The findings showed enhanced fibroblast density, increased collagen deposition, and improved vascularization. These results suggest that ESM is a safer and more effective alternative to ADMs in breast reconstruction, with the potential to revolutionize post-mastectomy care for breast cancer patients.
Keywords: Biocompatibility; Breast reconstruction; ISO 10993; Polymer; Safety; Silk protein; tissue regeneration

Engineered silk-dressing for acceleratedwound healing: biocompatibility and efficacy studies - Deshpande, Rucha; Pillai, Lakshmi R.; Sayyad, Raeesa; Shukla, Swati; Nisal, Anuya; Venugopalan, Premnath (Macromolecular Bioscience, 2025)
Advanced wound care dressings are essential for improving clinical outcomes. The present study investigates the wound management potential of a unique dressing fabricated from silk proteins. The dressing was characterized for its physical and structural properties, including surface texture, porosity, fluid absorption capacity, and moisture vapor transmission rate. These parameters have been found to be critical for optimal wound healing. In vivo full thickness wound healing studies in a rat model validated the efficacy of the Silk-dressing compared to conventional cotton gauze and commercial polyurethane foam dressings. Histopathological analysis confirmed improved re-epithelialization, collagen deposition, angiogenesis, and formation of secondary follicles. Key advantages of Silk-dressing included non-adherence, absorption of exudate, maintenance of optimal moisture at wound site and acceleratedwound closure. Biocompatibility studies were also conducted in accordance with ISO 10993 guidelines, demonstrating no cytotoxicity, irritation, sensitization, or pyrogenicity. These findings highlight the potential of this uniquely designed Silk-dressing as a superior alternative for wound management, with a potential to improve clinical outcomes.
Keywords: Biocompatibility; biopolymer; ISO 10993; Silk protein; wound Healing